Oceanic Birds of the World : a Photo Guide - Howell, Steve N. G.; Zufelt, Kirk (Princeton University Press, 2019)
A state-of-the-art photographic field guide to the world's oceanic birdsOceanic birds are among the most remarkable but least known of all birds, living at sea, far from the sight of most people. They offer unusual identification challenges--many species look similar and it can be difficult to get good views of fast-flying birds from a moving boat. The first field guide to the world's oceanic birds in more than two decades, this exciting and authoritative book draws on decades of firsthand experience on the open seas. It features clear text filled with original insights and new information and more than 2,200 carefully chosen color images that bring the ocean and its remarkable winged inhabitants to life. Never before have oceanic birds been presented in such an accessible and comprehensive way. The introduction discusses the many recent developments in seabird taxonomy, which are incorporated into the species accounts, and these accounts are arranged into groups that aid field identification. Each group and species complex has an introductory overview of its identification challenges, illustrated with clear comparative photos. The text describes flight manner, plumage variation related to age and molt, seasonal occurrence patterns, migration routes, and many other features. The result is an indispensable guide for exploring birding's last great frontier. A comprehensive, authoritative, and accessible guide to oceanic birdsCovers more than 270 speciesIncludes more than 2,200 color photos with concise captions noting key featuresFeatures careful species comparisons, overviews of the latest taxonomy, tips on how to observe and ID birds at sea, and much more.